A high-entropy high-temperature shape memory alloy with large and complete superelastic recovery. Issue 6 (3rd June 2021) - Li, Shaohui; Cong, Daoyong; Chen, Zhen; Li, Shengwei; Song, Chao; Cao, Yuxian; Nie, Zhihua; Wang, Yandong
ABSTRACT: High-temperature shape memory alloys (HTSMAs) show enormous potential for applications as energy conversion devices, actuators and sensors in automotive, aerospace, and energy exploration industries, but they suffer from strength decrease and microstructural instability at elevated temperatures, rendering it difficult to achieve satisfactory high-temperature superelasticity. Here, a novel Ti20 Hf15 Zr15 Cu25 Ni25 high-entropy HTSMA exhibiting large superelasticity with a fully recoverable strain of 4.0% at temperatures up to 285°C is designed with the high-entropy alloy concept by employing the sluggish diffusion and severe lattice distortion effects to suppress thermal softening. This work illuminates the design of novel high-performance functional materials for high-temperature applications. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A novel high-entropy high-temperature shape memory alloy exhibiting large complete superelastic recovery is designed by employing the sluggish diffusion and severe lattice distortion in high-entropy alloys to suppress thermal softening.